Multi-Phase Nano Fluid Natural Convection in A Partially Divided Cavity for Cooling of Radioactive Waste Containers - Peiravi, Mohammad Mohsen; Alinejad, Javad; Domiri Ganji, Davood (International Journal of Integrated Engineering, 2022)
The innovation of this investigation is fins arrangement effects on Al2O3-water Nano fluid natural convection in a partially divided cavity for energy storage systems and cooling of radioactive waste containers. Simulation of fluid velocity and temperature fields done based on the Lattice Boltzmann Model using the D2Q9 and D2Q5 methods, respectively. Streamline, isotherm, Nusselt number, velocity and temperature fields have been studied for different shapes of fins. In this investigation, we surveyed 4 shape of fins that arranged in three cases; case 1: yL=0.25 L, yR=0.75 L, case 2: yL=0.5 L, yR=0.5 L and Case 3: yL=0.75 L, yR=0.25 L. The results illustrated, assuming case 2: yL=0.5 L, yR=0.5 L is base case, so with changing arrangement of fins for case 1: yL=0.25 L, yR=0.75 L, rate percentage of average Nusselt number for cavities arranged with rectangular, circle, vertical and horizontal Ellipse fins were %26, %8, %4 and %8, respectively. Furthermore, with changing arrangement of fins to case 3: yL=0.75 L, yR=0.25 L, these percentages were %62, %24, %14 and %22.